2018
DOI: 10.2174/1381612824666180913151059
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Therapy for Ischemic Heart Disease: Advances and Challenges

Abstract: Ischemic heart disease (IHD) has been recognized as the main cause of mortality in the modern world. Application of cell therapy technologies for the IHD treatment has been actively studied from the beginning of 2000s. The review is dedicated to the use of mesenchymal stem cells (MSC) in the therapy of IHD. The strategies of the MSC modification in vitro for improvement of their regenerative potential are extensively discussed, including preconditioning to enhance the cell survival, boosting their paracrine ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The major benefit of MSC therapy is derived from the paracrine effects. The MSC secretome has cardiovascular protection effects and is known to modulate the death of residue cells caused by the pathological environment [17,76]. Nevertheless, even though MSCs show sufficient therapeutic potential in regeneration of damaged cardiomyocytes and ischemic heart diseases, there are still obvious limitations that should be overcome, including an incomplete understanding of the therapeutic mechanism, and low settlement and survival rates of the transplanted cells [79].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…The major benefit of MSC therapy is derived from the paracrine effects. The MSC secretome has cardiovascular protection effects and is known to modulate the death of residue cells caused by the pathological environment [17,76]. Nevertheless, even though MSCs show sufficient therapeutic potential in regeneration of damaged cardiomyocytes and ischemic heart diseases, there are still obvious limitations that should be overcome, including an incomplete understanding of the therapeutic mechanism, and low settlement and survival rates of the transplanted cells [79].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…The therapeutic effects of stem cell therapy in cardiovascular disease has been demonstrated not only in the various studies, but also in preclinical models where positive results have been reported [2,83]. However, there are apparent limitations that still need to be solved in order to utilize stem cell therapy in patients with cardiovascular disease [17]. In this regard, the introduction of additional genes reinforces the function of stem cells while still retaining the advantages of existing stem cell therapy.…”
Section: Limitations Of Stem Cell Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac interstitial cells, such as cardiac mesoangioblasts [11], are an appealing cell therapy source because of their beneficial paracrine effects on cardiac remodelling [12]. However, when injected directly into the myocardium or skeletal muscles, stem cells show very limited migration potential.…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow–derived mesenchymal stem cells (MSCs) can differentiate into cardiomyocytes (CMs) . Soluble paracrine factors, secreted by MSCs injected into animal models of cardiovascular disease, conferred cardioprotection by inducing neovascularization and regeneration . These soluble MSC paracrine factors can be produced by genetically engineered stem cells …”
Section: Introductionmentioning
confidence: 99%